Bibliometric Review of Artificial Intelligence in Project-Based Learning: Trends and Gaps in Social Sciences, Arts, and Humanities - Bramantya, Alfan; Pujiati, Eko; Kuswandi, Dedi; Fikri Aulia; Untari, Sri (Lembaga Sosial Rumah Indonesia, 2025)
Purpose – The rapid development of artificial intelligence (AI) has significantly transformed various aspects of human life, particularly in education. This study aims to examine trends in the use of AI within project-based learning (PjBL) strategies, specifically in the context of social, arts, and humanities topics, over the period of 2014–2024.Method – This study is a bibliometric review. The authors collected relevant research data from the Scopus database using the keywords (